Strategies to Increase Paddy Rice Production in Sugihwaras Village, Candi District, Sidoarjo Regency - AINI, NUR; AMIRIL, NUR; RENJAAN, IRENE PAULA; GAFURANINGTYAS, DEWI; GO, RATNA YULIKA; GO, RISKA TEZARA (Jurnal Teknologi Lingkungan, 2025)
Rice fields, which are cultivated with rice and produce rice, are a highly important food commodity for humans. Approximately 85% of the Indonesian population consumes rice as their staple food. The rice production in Sugihwaras Village, Candi Sub-district, Sidoarjo Regency, plays a crucial role in ensuring the availability of rice and improving the well-being of farmers. However, fluctuations in rice production and the decreasing agricultural land pose challenges for the farmers. This research aims to analyze strategies to increase paddy rice production in Sugihwaras Village, Candi District, Sidoarjo Regency. The analysis is conducted using the Internal-External (IE) matrix, which involves evaluating internal and external factors that influence paddy rice production. The internal factors evaluated include strengths and weaknesses, while the external factors encompass opportunities and threats. Based on the analysis results, several strategies are recommended to enhance paddy rice production in Sugihwaras Village. The recommended strategies include: strengthening farmers' skills and knowledge, optimizing land utilization and irrigation channels, improving accessibility and infrastructure, establishing and enhancing farmer groups, obtaining technical assistance, strengthening government support, and addressing challenges such as climate change. Then in the future, sustainable implementation of these strategies can improve paddy rice commodity production in Sugihwaras Village, provide economic benefits to farmers, and enhance the welfare of the local community. This research contributes to the development of agricultural commodity production enhancement strategies and can serve as a reference for relevant stakeholders in decision-making. Abstrak Sawah yang ditanami padi dan produksi beras merupakan komoditas makanan yang sangat penting bagi manusia. Sekitar 85% dari populasi Indonesia mengonsumsi beras sebagai makanan pokok. Produksi sawah di Desa Sugihwaras, Kecamatan Candi, Kabupaten Sidoarjo, memainkan peran penting dalam menjaga ketersediaan beras dan meningkatkan kesejahteraan para petani. Namun, fluktuasi dalam produksi padi dan menyusutnya lahan pertanian menjadi tantangan yang dihadapi oleh para petani. Penelitian ini bertujuan untuk menganalisis strategi peningkatan produksi komoditas padi sawah di Desa Sugihwaras, Kecamatan Candi, Kabupaten Sidoarjo. Analisis dilakukan dengan menggunakan matriks Internal-External (IE) yang melibatkan evaluasi faktor internal dan eksternal yang mempengaruhi produksi padi sawah. Faktor internal yang dievaluasi meliputi kekuatan (strenght) dan kelemahan (weakness), sedangkan faktor eksternal mencakup peluang (opportunities) dan ancaman (threats). Berdasarkan hasil analisis, beberapa strategi direkomendasikan untuk meningkatkan produksi padi sawah di Desa Sugihwaras yaitu memperkuat keterampilan dan pengetahuan petani, optimalisasi pemanfaatan lahan dan saluran irigasi, meningkatkan aksesibilitas dan infrastruktur, membangun dan meningkatkan kelompok tani, mendapatkan pendampingan teknis, memperkuat dukungan pemerintah, menghadapi tantangan seperti perubahan iklim. Kedepannya implementasi strategi ini secara holistik dan berkelanjutan dapat meningkatkan produksi komoditas padi sawah di Desa Sugihwaras, memberikan manfaat ekonomi bagi petani, dan meningkatkan kesejahteraan masyarakat setempat. Penelitian ini memberikan kontribusi dalam pengembangan strategi peningkatan produksi komoditas pertanian dan dapat menjadi acuan bagi pemangku kepentingan terkait dalam pengambilan keputusan.